1991
DOI: 10.1007/bf00167924
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of zinc by fungal mycelial wastes

Abstract: Waste mycelia from several industrial fermentation plants (Aspergillus niger, Penicillium chrysogenum, Clavicepspaspali) were used as a biosorbent for zinc ions from aqueous environments, both batchwise as well as in a column mode. With all mycelia tested, biosorption per biomass dry weight was a function of pH (increasing with increasing pH between 1.0 and 9.0), biomass concentration (decreasing at high biomass concentrations) and the zinc concentration. Under optimized conditions, A. niger and C. paspali wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(52 citation statements)
references
References 13 publications
2
45
0
5
Order By: Relevance
“…This shows that the biosorption mechanisms on fungal biomass surface is caused by interaction between heavy metals and different fungal species. Our results are similar to earlier studies which indicated the role of functional groups on fungal cell surface and the formation of complex bond among metal ions and various functional binding groups 18,19 . The rate of biosorption increased with increase in agitation speed ( Figure 5).…”
supporting
confidence: 93%
“…This shows that the biosorption mechanisms on fungal biomass surface is caused by interaction between heavy metals and different fungal species. Our results are similar to earlier studies which indicated the role of functional groups on fungal cell surface and the formation of complex bond among metal ions and various functional binding groups 18,19 . The rate of biosorption increased with increase in agitation speed ( Figure 5).…”
supporting
confidence: 93%
“…E.coli was found to be absent on all the sampling sites. Various microbial species, for example, microorganisms, fungi are known to be appropriate for adsorbing heavy metals on their surface and 1607 additionally aggregating inside their structure (Campbell and Martin, 1990;Luef, 1991;Mitani and Misic, 1991;Vinita and Radhanath, 1992). It has been shown that bacteria and fungi isolated from polluted environment are frequently tolerant to higher levels of metals than those isolated from unpolluted areas and that tolerant microorganisms are found at higher frequencies in polluted habitats.…”
Section: Results and Discussion:-mentioning
confidence: 99%
“…Padatan tersebut sebanyak 0,5 gram yang dibungkus dalam kertas saring direndam dalam larutan Zn 2+ dan dikocok menggunakan shaker dengan kecepatan 120 rpm selama beberapa jam. Sampling dilakukan setiap 30 menit sebanyak tiga kali dan masing-masing hasil sampling disentrifugasi pada kecepatan 4000 rpm selama 10 menit dan ditentukan konsentrasi Zn 2+ pada masing-masing perlakuan (Luef et al, 2004).…”
Section: Modifikasi Biomassa S Cerevisiaeunclassified
“…Perlakuan ini juga dapat melepaskan polimer polisakarida yang memiliki afinitas yang tinggi terhadap ion logam tertentu (Loaec, 1997). Perendaman biomassa dengan larutan NaOH terbukti telah meningkatkan kapasitas penyerapan Zn 2+ pada Aspergillus niger (Luef et al, 2004) pada permukaan sel melalui reaksi browning non-enzimatik akibat pemanasan (Loaec, 1997). Pemanasan ini juga berfungsi untuk mematikan S. cerevisiae.…”
Section: Modifikasi Biomassa S Cerevisiaeunclassified